Characteristic and Provenance of Talang Akar Formation Sandstone, Sukamoro Area, South Sumatera - Yogie Zulkurnia Rochmana; Idarwati Idarwati; Harnani Harnani; Elisabet Dwi Mayasari (Jurnal IPTEK, 2023)
Sukamoro area, Banyuasin Regency, South Sumatera, was the research location. This investigation focuses on the origin of sandstones from the Talang Akar Formation. In the area of investigation, sandstones are widely dispersed and exhibit a variety of properties. Due to the abundance of sandstones found and their high resistance and physical compactness, an analysis of the original rock can be carried out. Generally, the material that makes up sandstone comes from the previous rock. This investigation was undertaken using a descriptive-analytical methodology to determine the origin of the rock. The collected surface data is subsequently petrographically examined. After determining the composition of the constituent minerals, a provenance analysis was conducted to determine that the Talang Akar Formation's sandstones originated from the Magmatic Arc. Furthermore, the Talang Akar sandstone reveals the origin of the Recycle Orogen. Thus, it is considered that the sandstones of the Talang Akar Formation have seen many uplift episodes as a result of tectonic activity, almost to the point where they have experienced an increase in the maturity or stability of their continental block provenances